Prevalence and predictors of psychotropic medication use in adolescents and adults with autism spectrum disorder in Italy: A cross-sectional study. (June 2019) - Fusar-Poli, Laura; Brondino, Natascia; Rocchetti, Matteo; Petrosino, Beatrice; Arillotta, Davide; Damiani, Stefano; Provenzani, Umberto; Petrosino, Carmelo; Aguglia, Eugenio; Politi, Pierluigi
Highlights: We examined the use of psychotropic drugs in 195 adolescents and adults with ASD. 58.5% of the sample were using psychotropic medications. Antipsychotics were prescribed to nearly 40% of the sample. IQ, epilepsy, and psychiatric comorbidities predicted medication use. There is an urgent need for guidelines for adolescents and adults with ASD. Abstract: Autism spectrum disorder (ASD) is a group of life-long neurodevelopmental conditions with a prevalence of 1.5% in developed countries. Beside core symptomatology, ASD people are frequently affected by psychiatric comorbidities and behavioral problems. To date, only risperidone and aripiprazole have been approved for the pharmacological treatment of ASD-associated irritability in children and adolescents, while no guidelines exist for adults. The present cross-sectional study examined the prevalence and predictors of psychotropic medication use in 195 autistic subjects, aged between 14 and 58, treated in two Italian tertiary care centers. 58.5% of the sample were taking at least one medication; one third of the sample were on polypharmacotherapy. Antipsychotics were prescribed to 40% of the sample. Nearly 30% of the sample were on anticonvulsants/mood stabilizers. Both antidepressants and benzodiazepines were prescribed to approximately 16% of the subjects. IQ, epilepsy and psychiatric comorbidities were regarded as independent predictors of both mono- and polypharmacotherapy, while severity of repetitive behaviors predicted only polypharmacotherapy. Our data highlighted that medications prescribed to adolescents and adults with ASD are heterogeneous and often rely only on clinicians' experience. Future research should investigate the effectiveness of psychotropic drugs in this specific population, to promote the development of appropriate treatment guidelines.